Lung Cancer Targeted Chemoradiotherapy via Dual-Stimuli Responsive Biodegradable Core-Shell Nanoparticles - Roshni Iyer; Harish Ramachandramoorthy; Trinh Nguyen; Cancan Xu; Huikang Fu; Tanviben Kotadia; Benjamin Chen; Yi Hong; Debabrata Saha; Kytai Truong Nguyen (MDPI AG, 2022)
Lung cancer is one of the major causes of cancer-related deaths worldwide, primarily because of the limitations of conventional clinical therapies such as chemotherapy and radiation therapy. Side effects associated with these treatments have made it essential for new modalities, such as tumor targeting nanoparticles that can provide cancer specific therapies. In this research, we have developed novel dual-stimuli nanoparticles (E-DSNPs), comprised of two parts; (1) Core: responsive to glutathione as stimuli and encapsulating Cisplatin (a chemo-drug), and (2) Shell: responsive to irradiation as stimuli and containing NU7441 (a radiation sensitizer). The targeting moieties on these nanoparticles are Ephrin transmembrane receptors A2 (EphA2) that are highly expressed on the surfaces of lung cancer cells. These nanoparticles were then evaluated for their enhanced targeting and therapeutic efficiency against lung cancer cell lines. E-DSNPs displayed very high uptake by lung cancer cells compared to healthy lung epithelial cells. These nanoparticles also demonstrated a triggered release of both drugs against respective stimuli and a subsequent reduction in in vitro cancer cell survival fraction compared to free drugs of equivalent concentration (survival fraction of about 0.019 and 0.19, respectively). Thus, these nanoparticles could potentially pave the path to targeted cancer therapy, while overcoming the side effects of conventional clinical therapies.